2004
DOI: 10.1209/epl/i2003-10273-1
|View full text |Cite
|
Sign up to set email alerts
|

Spin-dependent magnetoresistance in multiwall carbon nanotubes

Abstract: The spin-dependent transport in multiwall carbon nanotubes obtained by chemical vapor deposition (CVD) in porous alumina membranes is studied. The zero bias anomaly is found to verify the predicted Luttinger liquid power law. The magnetoresistance at high fields varies in sign and amplitude from one sample to the other, which is probably due to the presence of dopant in the tube. In contrast, the magnetoresistance due to the spin polarized current is destroyed in the nanotube as expected in case of spin-charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…In recent years, also spin transport through quantum dots formed by nanotubes, molecular systems or nanoparticles has started to attract attention both experimentally 2,3,4,5,6,7,8 and theoretically. 9,10,11,12,13,14,15,16 One of the motivations for this has been the possibility of using quantum dots with a single spin as qubits, but naturally also a number of fundamental questions arise on how the interplay of spin coherence and interactions influences the transport.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, also spin transport through quantum dots formed by nanotubes, molecular systems or nanoparticles has started to attract attention both experimentally 2,3,4,5,6,7,8 and theoretically. 9,10,11,12,13,14,15,16 One of the motivations for this has been the possibility of using quantum dots with a single spin as qubits, but naturally also a number of fundamental questions arise on how the interplay of spin coherence and interactions influences the transport.…”
Section: Introductionmentioning
confidence: 99%
“…An other characteristic is that the temperature dependence of the conductance is a power law of the form G(T ) = G 0 T −α , where α is around 0.3. But the most striking result is that all data at different V bias and temperatures collapse on a unique curve [190], Figure 17. This is the manifestation of a scaling law; the quantity GT −α is a function of the variable eV/kT.…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…Alumina membranes are a very widely used template for the growth of carbon nanotubes [109][110][111][112][113][114][115][116][117][118][119][120]147,[186][187][188][189]. Multi-wall carbon nanotubes (MWNT) were grown by a CVD reaction in the porous of alumina for transport measurements, Figure 16 [190]. The alumina membranes were made, as previously described, by anodization of aluminium in 0.3 mol/l oxalic acid at 40 volts for 10 minutes, depending on the desired length.…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…Spintronics devices exploiting the spin of the electron [1][2][3][4][5][6][7][8][9][10] are prepared to revolutionise the electronics industry. The significance of this new generation device is faster memory and lower power consumption at low electron density.…”
Section: Introductionmentioning
confidence: 99%
“…Yakushiji et al [22] experimentally demonstrated the influence of spin conduction on TMR. The enhancement and oscillation of TMR in ferromagnetic multiple junctions have been predicted by several authors [23][24][25][26][27][28][29][30]. However, there have been only a few experiments on spin-dependent single electron tunnelling (SET) to date [31][32][33][34][35][36] due to the difficulty in fabricating appropriate sample structures for spin-dependent SET.…”
Section: Introductionmentioning
confidence: 99%